2010
DOI: 10.1128/cvi.00062-10
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a 13-Valent Pneumococcal Conjugate Vaccine Compared to Those of a 7-Valent Pneumococcal Conjugate Vaccine Given as a Three-Dose Series with Routine Vaccines in Healthy Infants and Toddlers

Abstract: A 13-valent pneumococcal conjugate vaccine (PCV13) has been developed to improve protection against pneumococcal disease beyond that possible with the licensed 7-valent vaccine (PCV7). This study compared the safety and immunogenicity of PCV13 with those of PCV7 when given as part of the pediatric vaccination schedule recommended in Italy. A total of 606 subjects were randomly assigned to receive either PCV13 or PCV7 at 3, 5, and 11 months of age; all subjects concomitantly received diphtheria-tetanus-acellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 41 publications
(43 reference statements)
4
63
0
1
Order By: Relevance
“…However, the net vaccine benefit has been negatively affected by a 71% increased rate of invasive pneumococcal disease caused by nonvaccine serotypes (30). Recently, a 13-valent pneumococ-cal conjugate vaccine (PCV-13) was developed to further improve protection (9,19) by covering the serotypes that most frequently cause infection and colonization. However, the increase in carriage of nonvaccine serotypes, and the associated increase in invasive disease, could ultimately outweigh the benefits of the current PCV (21).…”
mentioning
confidence: 99%
“…However, the net vaccine benefit has been negatively affected by a 71% increased rate of invasive pneumococcal disease caused by nonvaccine serotypes (30). Recently, a 13-valent pneumococ-cal conjugate vaccine (PCV-13) was developed to further improve protection (9,19) by covering the serotypes that most frequently cause infection and colonization. However, the increase in carriage of nonvaccine serotypes, and the associated increase in invasive disease, could ultimately outweigh the benefits of the current PCV (21).…”
mentioning
confidence: 99%
“…[18][19][20][21] WHO ELISA responder rates at 0.35 μg/ mL for the non-PCV7 serotypes of PCV13 were also compared to those of PCV7. In addition, exploratory analyses demonstrated that functional antibody titers were elicited by all the additional serotypes of PCV13.…”
Section: 17mentioning
confidence: 99%
“…PCV10 added three additional serotypes-1, 5 and 7F-plus a Non-Typeable Haemophilus influenzae (NTHi) protein carrier that could protect against AOM [11]. PCV13 covers an additional three-3, 6A and 19A (i.e., six more than PCV7) [12]. Evidence shows that their safety and immunogenicity profiles of these higher valences vaccines are similar to that of PCV7 and they do not interference with other vaccines in young children [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…PCV13 covers an additional three-3, 6A and 19A (i.e., six more than PCV7) [12]. Evidence shows that their safety and immunogenicity profiles of these higher valences vaccines are similar to that of PCV7 and they do not interference with other vaccines in young children [11,12]. Since these two higher valence vaccines differ in serotypes covered, NTHi protein carrier, and unit price per dose, their impact as a public health intervention could differ.…”
Section: Introductionmentioning
confidence: 99%